Total Quality Management Its importance, requirements, and some application criteria and obstacles in general education according to selected references - ALramadneh, Nehad Hassan (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the importance of adopting total quality management systems in education for the development of education, The study took many selected references in total quality management. Where the study began with an introduction that included the definition of total quality and the reasons for its interest. Then it focused on the principles of quality improvement, its objectives, the benefits of their application in education, and the justifications for the necessity of adopting quality systems in education. The study also included the obstacles to the application of total quality and the factors for achieving success in quality management. Where the study found a low level of quality in public education, and this necessitates the need to work to raise the level of quality in education, this necessitates the necessity of working to raise the level of quality through holding training programs for total quality management in order to raise awareness of the importance of adopting quality in education and introducing quality concepts, principles, objectives and how to apply them, In addition to the necessity of conducting other studies on total quality in public education and comparing their results in order to take the necessary measures to adopt quality in education.
Keywords: total quality management; public education